The Impact of Regulatory Capital on Risk Taking By Pakistani Banks: An Empirical Study - Muhammad Sajjad Hussain; Dr. Muhammad Muhaizam Musa; Dr. Abdelnaser Omran (SEISENSE Journal of Management, 2019)
Objective - The objective of this study is to examine the relationship between capital regulation and risk-taking by the banks of Pakistan. Design - This study was conducted on all the commercial banks of Pakistan and data were collected from the year 2005 to 2016. Findings - This study concluded the significant positive relationship between regulatory capital and risk-taking by banks in Pakistan. The findings of this study play a key role in the implementation of capital regulations in the banks of developing countries. Policy Implications - In the light of this study, the regulators must revise their implementation process of the Basel Accord capital regulations in the banks of developing countries. The prime intention of regulators are only on to maintain the minimum capital ratios but must be conscious of other important elements of capital regulation implications. Originality - This study is one of the first attempts that investigated the crucial role of regulatory capital towards risk-taking in the Pakistani context.